Diverse reactivity of carbenes and silylenes towards fluoropyridines - Kundu, Gargi; Ajithkumar, V. S.; Bisai, Milan Kumar; Tothadi, Srinu; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2- as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C-F bond activation leaving C-H bonds intact (5b). The reaction of SIDipp with C5F5N in the presence of BF3 afforded the ring cleavage product (3). Analogous reactions with silylene led to oxidative addition at the Si(II) center.